Prediction of potential habitat of Verbena officinalis in China under climate change based on optimized MaxEnt model - Chen, Shimao; Jiang, Zixuan; Song, Jia; Xie, Tao; Xue, Yu; Yang, Qingshan (Frontiers in Plant Science, 2025)
Verbena officinalis is an important medicinal plant widely used in traditional Chinese medicine for the treatment of rheumatism, insomnia, and liver and gallbladder diseases. Its resources primarily rely on wild populations, which are insufficient to meet the increasing market demand. Furthermore, climate change exacerbates the uncertainty of its distribution range. This study employs an optimized MaxEnt model to predict the potential distribution of V. officinalis under current and future climate scenarios in China. Based on 445 effective occurrence records and 90 environmental variables (covering climatic, soil, and topographic factors), the study selected key variables influencing the distribution through correlation analysis and variable contribution rates, and optimized model parameters to improve prediction accuracy (AUC = 0.934). Results showed that, under current climate conditions, the total suitable habitat area of V. officinalis is 2.06 × 106 km2, accounting for 21.39% of China’s land area, mainly distributed in central, eastern, and southern China. The minimum temperature of the coldest month (bio_6, contribution rate 72.8%) was identified as the key factor influencing distribution, while November precipitation (prec_11) and annual temperature range (bio_7) also played important roles. Under future climate change scenarios (SSP1-2.6 and SSP5-8.5), the total suitable habitat area shows an overall increasing trend, reaching a maximum in the 2070s under the high-emission scenario (an increase of 3.6 × 105 km2 compared to the current distribution). Expansion was primarily observed in northern high-latitude regions. The geometric centroid of suitable areas demonstrated a significant northward shift, reflecting the adaptive expansion potential of V. officinalis in response to warming climates. This study highlights the significant impact of temperature and precipitation on the distribution of V. officinalis and provides scientific evidence for its conservation, cultivation planning, and sustainable development in the context of climate change.